2019
DOI: 10.3390/rs11131579
|View full text |Cite
|
Sign up to set email alerts
|

Power Pylon Reconstruction Based on Abstract Template Structures Using Airborne LiDAR Data

Abstract: As an important power facility for transmission corridors, automatic three-dimensional (3D) reconstruction of the pylon plays an important role in the development of smart grid. In this study, a novel three-dimensional reconstruction method using airborne LiDAR (Light Detection And Ranging) point cloud is developed and tested. First, a principal component analysis (PCA) algorithm is performed for pylon redirection based on the structural feature of the upper part of a pylon. Then, based on the structural simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…Recently, there have been several high-quality algorithms focusing on 3D object reconstruction. However, according to our knowledge, the automatic image-based reconstruction of pylon has rarely been reported, and only a few works research automatic pylon reconstruction based on ALS data [10][11][12][13]. Li et al first proposed a model-driven method to reconstruct the pylon [10].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, there have been several high-quality algorithms focusing on 3D object reconstruction. However, according to our knowledge, the automatic image-based reconstruction of pylon has rarely been reported, and only a few works research automatic pylon reconstruction based on ALS data [10][11][12][13]. Li et al first proposed a model-driven method to reconstruct the pylon [10].…”
Section: Related Workmentioning
confidence: 99%
“…The pylon body is reconstructed by a data-driven strategy, and the pylon head is efficiently reconstructed by a model-driven strategy using a Metropolis-Hastings sampler coupled with a simulated annealing algorithm, which reduces the number of parameters and searching space. Chen et al divided the pylon into three parts: inverted triangular pyramid lower structures, quadrangular frustum pyramid middle structures and complex upper structures [12]. The prior knowledge with a data-driven strategy is applied to reconstruct the lower and middle structures and the priori abstract template structures are used to reconstruct the upper structures.…”
Section: Related Workmentioning
confidence: 99%
“…More recently, case studies of power pylons are reported, which are bigger and more complex objects than cell towers. In (Chen et al, 2019) Airborne Laser Scanners (ALS) are used to acquire 3D data, and an automatic reconstruction algorithm is developed to retrieve the frame of the quadrangular frustrum pyramid, while the internal structure reconstruction is based on prior knowledge of it. In (Jiang.…”
Section: Related Workmentioning
confidence: 99%
“…Airborne laser scanning (ALS) is an active remote sensing technology that can directly and efficiently acquire the three-dimensional spatial information of objects. It is widely used in digital city construction [3,4], forestry surveys [5,6], and power line inspection [7][8][9][10][11][12]. ALS eliminates some of the limitations of traditional inspection, such as high labor intensity, low efficiency, and low accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Since they are complex and diverse, multiple pylon models using a variety of parameters to describe the shape, need to be considered for this class. Thus, this leads to low adaptability and high complexity of the algorithm [11]. For the power line class, the defined rules mainly depend on the elevation, resulting in poor noise immunity.…”
Section: Introductionmentioning
confidence: 99%